Medical Rhetoric in Training Pediatricians - Elena N. Grinko ("Paediatrician" Publishers LLC, 2016)
Rhetoric studies can play a positive role in the formation of verbal and cogitative activity and communicative competence of the future pediatrician. The latest scientific researches evidenced that the success of a doctor's practice is related not only to his highly professional medical knowledge, but also to his ability to talk, persuade, and communicate. Rhetoric is the theory and practice of the effective verbal expression of a thought in terms of a public monologue and dialogue; Medical (private) rhetoric is aimed at the development of general and professional verbal, cogitative, and communicative abilities of the future doctor. Methodically competent combination of disciplines «Medical Rhetoric» and «Psychology and Pedagogy» into a single module can enhance educational outcomes in teaching students.